Jawor. Atlas of historical sources - Nowosielska-Sobel, Joanna; Strauchold, Grzegorz; Wiszewski, Przemysław (Publishing House eBooki.com.pl, 2018)
The authors od the book presented here focuses their attention on one city, in contrast to previous volumes of the series dealing with the issue of settlement complexes, which nowadays are actual municipalities. The choice of Jawor as the subject of this publication was not accidental. As in the monograph of the history of the city, here we wanted to supplement our knowledge about the functioning of the communities of the southern outskirts of Silesia. And in this publication weare dealing with modes of perceiving of an urban landscape. In this series we usually deal with communities of local importance, but to compare results of previously done analysis the choice fell on a city with well recognized importance and potential, but not necessarily of today's first-rate administrative significance. The history of perceiving spatial transformations of Jawor as the capital of the duchy and a potential model for other urban settlements in the south of Silesia enables us to better understand the historical processes based on description and construction of spaces that have occurred in territories located far from political centre of the region.
Keywords: Jauer; maps; local history; regional history; Silesia; spatial history; imagined geography